2013
DOI: 10.1017/s0022215113003071
|View full text |Cite
|
Sign up to set email alerts
|

Throat-related quality of life in peritonsillar abscess sufferers: application of the adult tonsil outcome inventory

Abstract: Peritonsillar abscess had a significant impact on throat-related quality of life. In many, peritonsillar abscess represented an acute episode on a background of chronic throat problems. For optimal management, notably the place and timing of tonsillectomy, this impact should be taken into account. The adult tonsil outcome inventory is an ideal tool for use in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Still, 88% of our surgical patients achieved an improvement of at least 10.0 points, which we found to be the MIC value indicating that, despite lower TOI-14 levels at entry, the vast majority of our patients benefitted from tonsillectomy. We found that the mean TOI-14 score in the normal population (5.0, 3.6-6.4) coincides with the findings of both Skevas et al [1] and Powell et al [3] We utilized a matched cohort design, which guaranteed similar methods and timing of data collection and thus reduced the risk of bias when the surgical and control subjects were compared. The TOI-14 instrument was translated into Finnish and psychometrically validated according to the recommendations of the two distinguished societies (ISO-QOL and COSMIN).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Still, 88% of our surgical patients achieved an improvement of at least 10.0 points, which we found to be the MIC value indicating that, despite lower TOI-14 levels at entry, the vast majority of our patients benefitted from tonsillectomy. We found that the mean TOI-14 score in the normal population (5.0, 3.6-6.4) coincides with the findings of both Skevas et al [1] and Powell et al [3] We utilized a matched cohort design, which guaranteed similar methods and timing of data collection and thus reduced the risk of bias when the surgical and control subjects were compared. The TOI-14 instrument was translated into Finnish and psychometrically validated according to the recommendations of the two distinguished societies (ISO-QOL and COSMIN).…”
Section: Discussionsupporting
confidence: 54%
“…Despite the fact that chronic throat-related diseases are common, disease-specific quality-of-life (QoL) instruments for these illnesses are scarce. For adults with chronic tonsillitis, we have merely the Tonsillitis Outcome Inventory-14 (TOI-14), which was developed and validated in German by Skevas et al [1] In addition to the validation studies reported by Skevas et al, Roplekar et al reported that preoperative TOI-14 scores were high among tonsillectomy candidates and Powell et al showed similarly raised scores among peritonsillar abscess sufferers [2,3]. Still, we need more information particularly on interpretation of the TOI-14 scores.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in HRQoL outcomes after tonsillectomy may considerably vary depending on the study cohort and the questionnaire used. In surveys using the GBI or the Adult Tonsil Outcome Inventory, gender had no effect on HRQoL outcomes [ 28 , 29 ]. On the other hand, Plath et al found that female gender resulted in higher socioeconomic item subscores when using the Tonsillectomy Outcome Inventory 14 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have shown the TOI-14 to have discriminant validity in a comparison of recurrent tonsillitis patients with healthy volunteers 68 and in peritonsillar abscess. 69,70 Importantly, tonsillitis is a disease primarily of younger adults, usually with education or workplace activity profiles. Small descriptive series report substantial benefits in reduction in days lost from work or education following tonsillectomy.…”
Section: Assessment Of Baseline Sore Throat Severitymentioning
confidence: 99%